Australian animals - Arnold, Caroline (New York : HarperCollins, 2000)
Depicts the many animals that live in the diverse habitats of Australia, including forest, grassland, desert, and seacoast.
Keywords: Zoology -- Australia -- Juvenile literature; Zoology -- Australia